How Will the SCOTUS Affirmative Action Ruling Affect the Integrity of University Leaders? - Woodard, Megan R.; Perry, Eretta Y. Brown; Barnes, Cari V.; McClary, Ashley A.; Bell, Reginald L. (Journal of Leadership, Accountability and Ethics, 2024)
On June 29, 2023, the Supreme Court of the United States (“SCOTUS”) ruled on addressing the legality of race-conscious affirmative action in college admissions programs in Students for Fair Admission, Inc. Based on the ruling, our study examined the literature to answer one research question: How will the SCOTUS affirmative action ruling affect the integrity of university leaders? We now understand how post-affirmative action could affect the integrity of university leaders. We now know more about (1) leaders’ perspectives post-SCOTUS ruling, (2) leaders’ influences on the educational culture, and (3) the effects that leaders’ integrity could have after the SCOTUS Title VI 2023 ruling. We make five conjectures about what we believe will guide university leaders’ integrity post-SCOTUS ruling.